College Women's Memorable Sexual Messages From Mothers, Fathers, Friends/Peers, and Online Media: A Mixed-Methods Latent Class Analysis. Issue 1 (February 2023) - Astle, Shelby; Anders, Kristin; Shigeto, Aya; Rodriguez, Kristin
This study used a mixed-methods approach to examine the memorable sexual messages emerging adult women received from mothers, fathers, friends/peers, and online media in their lifetime, and the patterns in which these messages were received. Our sample included 192 college-attending women (81.8% heterosexual, 57.3% White) ages 18–25 ( M = 19.4, SD = 1.4) from a southeastern U.S. university. Through content analysis of open-ended responses to an online survey, we identified ten main categories of memorable sexual messages. The majority focused on pregnancy/STI avoidance, sexual violence avoidance, no messages, sex positive messages, and waiting, with varying frequencies across sources. Results of a latent class analysis showed six distinct classes of messages received, with the largest class reporting no memorable messages from all sources. These results indicate that some emerging adult women receive similar messages and others conflicting messages from different sources that can shape their sexual development. We discuss implications for programming.